Cyclooxygenase-2 immunohistochemical expression in serrated polyps of the colon - Kiedrowski, Miroslaw; Mroz, Andrzej; Kraszewska, Ewa; Rembiszewska, Alina; Felisiak-Golabek, Anna; Kupryjanczyk, Jolanta; Deptala, Andrzej; Orlowska, Janina (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study : Cyclooxygenase-2 (COX-2) expression has been observed in a substantial percentage of classical adenomas of the large bowel. The aim of the study was to assess and compare the expression of COX-2 in serrated polyps of the colon. Material and methods : One hundred and nineteen serrated polyps were analyzed. There were 83 hyperplastic polyps (HP), 19 sessile serrated polyps (SSP) and 17 traditional serrated adenomas (TSA). COX-2 expression was assessed semi-quantitatively (0–2) and each lesion was fully characterized in terms of anatomical location, size, histology, age and sex of the patient. The general estimating equation (GEE) model with logit link was used in the statistical analysis. Results : Epithelial expression of COX-2 was found in 85/119 serrated polyps (71.43%): 57/83 (68.67%) HP, 16/19 (84.21%) SSP, and 12/17 (70.59%) TSA. In HP and SSP it was predominantly of weak (49/83 HP, 12/19 SSP), whereas in TSA it was mainly of medium/strong intensity (8/17). The TSA category was associated with more frequent COX-2 expression (OR = 7.00, 95% CI: 1.49–32.88, p = 0.014) than HP, but such relation was not found for SSP vs. HP (p > 0.1). No associations between COX-2 expression and clinical parameters were found. Conclusions : Immunohistochemical COX-2 expression cannot serve as a diagnostic adjunct to differentiate HP and SSP.